1992
DOI: 10.1172/jci115689
|View full text |Cite
|
Sign up to set email alerts
|

Protein C inhibitor in human body fluids. Seminal plasma is rich in inhibitor antigen deriving from cells throughout the male reproductive system.

Abstract: An assay was developed for the measurement of human protein C inhibitor antigen (PCI) in blood plasma and other biological fluids. Both native PCI, modified inhibitor, and complexes of inhibitor with activated protein C or plasma kallikrein could be measured with the assay. Inhibitor antigen concentrations were found to be very high in seminal plasma (> 200 mg/liter), more than 40 times the concentration of PCI found in blood plasma. The inhibitor in seminal plasma was unable to form complexes with activated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
119
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(133 citation statements)
references
References 43 publications
14
119
0
Order By: Relevance
“…Maintenance of the copulatory plug, for instance, may require that the high levels of uPA synthesized by the vas deferens and the seminal vesicle, and present in semen and on ejaculated spermatozoa, be subjected to a tight inhibitory control, possibly through the activity of PN-I. In addition, PCI, a serpin distinct from PN-I but which is also an inhibitor of uPA, tPA and thrombin, has recently been identified in human seminal plasma and seminal vesicles (Espafia et al, 1991;Laurell et al, 1992); whether PN-I is present in the human genital tract, or whether PCI may play in humans a role similar to that of PN-I in rodents, is at present not known.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance of the copulatory plug, for instance, may require that the high levels of uPA synthesized by the vas deferens and the seminal vesicle, and present in semen and on ejaculated spermatozoa, be subjected to a tight inhibitory control, possibly through the activity of PN-I. In addition, PCI, a serpin distinct from PN-I but which is also an inhibitor of uPA, tPA and thrombin, has recently been identified in human seminal plasma and seminal vesicles (Espafia et al, 1991;Laurell et al, 1992); whether PN-I is present in the human genital tract, or whether PCI may play in humans a role similar to that of PN-I in rodents, is at present not known.…”
Section: Resultsmentioning
confidence: 99%
“…oal-protease inhibitor, a2-antiplasmin and antithrombin III, belong to a different class of antiproteases, the serpins (Huber and Carrell, 1989). Recently, the synthesis of the serpin protein C inhibitor (PCI) by the human male reproductive system has been described (Espania et al, 1991;Laurell et al, 1992). The production of other serpins by male genital tract organs has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…PCI is synthesized in the liver, testis, prostate, and kidney (31,32). It is of interest that TM has been observed on several cell types not in contact with blood (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Seminal fluid protease inhibitors have been identified in a wide range of organisms from insects to mammals (e.g., Laurell et al 1992;Ohlsson et al 1995;Murer et al 2001;Swanson et al 2001;Kotlowska et al 2005), suggesting that protease inhibitors play significant and possibly conserved roles in reproduction. Interestingly, comparative structural modeling has revealed that the mammalian and Drosophila seminal fluid protease inhibitors are similar in predicted protein structures and hence likely to share biochemical functions (Mueller et al 2004).…”
mentioning
confidence: 99%